Waria Dalam Pandangan Islam - Nadia, Zunly (Musawa Jurnal Studi Gender dan Islam, 2003)
The existence of transvestism is something that cannot be denied, even though these tendencies represent symptoms of sexual abnormality. From this point, many views have emerged regarding transvestites. This article endeavours to explain the various forms of this phenomenon including homosexuality, transvestism and transsexuality, and the differences between them. It then goes on to review the Islamic laws concerning these by putting forward argumentation and quoting the hadith of the Prophet.